An interventional study to assess the effectiveness of ‘WhatsApp’ as a teaching learning tool in community medicine - Dyavarishetty, Padmavathi V.; Patil, Dipak C. (International Journal Of Community Medicine And Public Health, 2017)
Background:Undergraduate medical students, perceive the subject of Community Medicine as irrelevant to their role as physician and majority of the students dislike the subject and consider it as dull and boring. The present research study aims to study the effectiveness of ‘WhatsApp’ as medium of teaching complementing the traditional teaching to enhance the knowledge and skills of the undergraduate medical students using case based learning. Methods:Before and after comparison Interventional study design amongst 49 sixth semenster students conducted over a period of six months in a private medical college. Implementation of the study divided into three phases – preparatory, intervention and evaluation phase. Results:The improvement in average marks scored for epidemiology module was 1.97 and that for diabetes module was 5.38 which were statistically significant. The participation rate for the various modules ranged from as low as 10.2% to 73.5%. About 90% students perceived ‘WhatsApp’ as an effective tool for teaching-learning; a tool that stimulates and encourages learning. Conclusions:There was a significant improvement in knowledge amongst the students. Though perceived as an effective tool for learning by the students, participation rate in online discussion was poor over the course of implementation.